Духless 21 века. Селфи: [роман] / Сергей Минаев - Минаев Сергей Сергеевич (АСТ, 2015)
Экземпляры: Ф-6 (20150825) / Инвентарный номер: 48800 / Цена: 313.88 / Сис.шифр: Р2 / Авт.знак: М 61 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44